Introduction. Issue 1 (2nd January 2022) - Hyun, Jaehwan
Abstract: In the latest issue's "Editor's Note" of EASTS, Wen-hua Kuo made a call to East Asian science studies scholars to commit to an archeology of the social and technical infrastructure of epidemics. Coincidently, ten historians and sociologists working on science, technology, medicine, and environment with a focus on China, Japan, Taiwan, Singapore, and South Korea had just begun a collective effort to understand how face masks had become the most important part of the current pandemic governance in East Asia. As its first step, a virtual workshop, "The Socio-Material History of Masked Societies in East Asia, " was held at the Max-Planck Institute for the History of Science on 26 October 2020. This forum aims to introduce the virtual meeting's outcome to the wider EASTS community and encourages them to engage with the collaborative enterprise to investigate the history of masks. All papers focus on the socio-material dimension of masks while problematizing current culturalist explanatory narratives about "masked societies" in East Asia. By doing so, the papers show how mask use is closely linked to heterogenous but interconnected entanglements of environmental governance, political movements, and risk cultures in East Asian polities. It interrogates these relationships in the context of scientific controversies and quarantine regimes.